Optimizing method of nursing teaching in the Central Sterile Supply Department (消毒供应中心护理带教方法优化实践与分析) - LI Haiqing (李海青); WANG Yuena (王岳娜); REN Juanxia (任娟霞); XU Yuanle (许远乐) (Journal of International Translational Medicine Limited, 2022)
Objective To evaluate the optimization in teaching method of nursing teaching in the Central Sterile Supply Department. Methods Totally 300 nursing students participating in internship program in the Central Sterile Supply Department between July 2020 and May 2021 were recruited as the research objects. According to the internship plan, nursing students were arranged into two groups: 150 nursing students in the control group received routine nursing teaching methods, and 150 nursing students in the study group received an optimized method of nursing teaching. The job skills of nursing students and their satisfaction with nursing teaching were measured. Results The score of job skills assessments was increased in both control group and study group at the end of internship, and assessment score in the study group was higher than that in the control group(P＜0. 01). The satisfaction rate in the in the study group was higher than that in the control group (P＜0. 05). Conclusion Application of the optimized method is effective to improve the nursing teaching quality in the Central Sterile Supply Department. It presents an opportunity for nursing students to practice their job competence and skills. (目的 探讨消毒供应中心护理带教方法优化和实践效果。方法 选取2020年7月-2021年5月在医院消毒供应中心实习的300名护理实习生为研究对象, 根据实习时间分为对照组和研究组, 各150名。对照组护理实习生接受常规带教, 将优化后的带教方法用于研究组护理实习生带教中。考核两组护理实习生岗位技能操作能力, 评估护理实习生对带教质量的满意程度。结果 实习结束后, 两组护理实习生岗位技能操作能力考核评分均较实习前提高, 且研究组护理实习生评分高于对照组, 差异有统计学意义(P＜0. 01)。研究组护理实习生对护理带教的总满意高于对照组的(P＜0. 05)。结论 优化消毒供应中心护理带教方法可以提升护理带教质量, 培养护理实习生岗位技能。)